2010
DOI: 10.1007/s10616-010-9288-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Korean white ginseng extracts on obesity in high-fat diet-induced obese mice

Abstract: The present study examined the antiobesity effect and mechanism of action of Korean white ginseng extracts (KGE) using high-fat diet (HFD)-induced obese mice. Mice were fed a low-fat diet (LFD), HFD or HFD containing 0.8 and 1.6% (w/ w) KGE diet (HFD ? 0.8KGE and HFD ? 1.6KGE) for 8 weeks. We also examined the effects of KGE on plasma triglyceride (TG) elevation in mice administrated with oral lipid emulsion. Body weight gain and white adipose tissue (WAT) weight were significantly decreased in the HFD ? 1.6KG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 46 publications
3
40
0
1
Order By: Relevance
“…These extracts are known to improve blood flow, relieve fatigue, and attenuate oxidative stress in the body [8917]. Furthermore, Lee et al [18] reported that Korean white ginseng extracts regulated lipogenesis-related gene expressions in white adipose tissues, inhibited intestinal fat absorption, and reduced body weight.…”
Section: Discussionmentioning
confidence: 99%
“…These extracts are known to improve blood flow, relieve fatigue, and attenuate oxidative stress in the body [8917]. Furthermore, Lee et al [18] reported that Korean white ginseng extracts regulated lipogenesis-related gene expressions in white adipose tissues, inhibited intestinal fat absorption, and reduced body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Our evidence suggests that the 20% RMR-LM extract may decrease lipogenesis partly by regulating PPARγ signaling. SREBP-1 is a major transcription factor involved in the activation of lipogenic genes such as FAS and ACC (22,23). As the hepatic SREBP-1 mRNA level was significantly lower in the 10% RMR-LM group and 20% RMR-LM group than in the control group, this lower SREBP-1 level could have contributed to the reduction in the FAS and ACC mRNA levels in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…24) Korean white ginseng extracts showed a decrease of FAS expression in white adipose tissue of high-fat diet-induced obese mice. 25) Korean ginseng powder affected a lowering of the serum total cholesterol level by inhibiting HMG-CoA reductase activity in avian liver. 26) Lee et al reported that KRG improved insulin sensitivity with AMPK activation in OLETF rats.…”
Section: )mentioning
confidence: 99%